Metaphorical Translation in Adonis's Janāzatu Imra’atin Poem - Umi Nurun Ni'mah; Tika Fitriyah (Insyirah: Jurnal Ilmu Bahasa Arab dan Studi Islam, 2025)
The research of translating metaphors in poetry holds significance in academia due to its consideration of the resemblances between the source and target languages in poetry translation, encompassing not just semantic meaning but also formal structure. This study is descriptive-qualitative research that aims to categorize the metaphorical expressions within the "Janāzatu Imra'atin" poem authored by Adonis and its translation by Faza Binal Alim, while also delving into their respective meanings. Moreover, this research examines the strategies utilized by the translator to convey metaphors for the target language. The theoretical framework adopted in this research is based on the concept of metaphor and its translation processes as proposed by Newmark. The data of this research totaled 29 data taken using purposive sampling technique. The result of this research shows that the type of metaphor in Janāzatu Imra'atin poem is original metaphor. These metaphors are specifically created by the author to describe the message he wants to convey. The metaphor translation procedures found in this research are 1) translation of metaphor into metaphor with the same image and meaning; this procedure is used in the data by 83%, 2) translation of metaphor into the same metaphor in the target language, combined with the meaning, or given additional information; this procedure is used in the data by 14% 3) a combination of translating metaphor with metaphor, but some words are deleted or not translated; this procedure is used in the data by 3%. The results show that translators try to translate metaphors as accurately as possible, so most metaphor forms and meanings are translated into the same form in the target language. Future research is expected to further connect the aspects of translation, culture, and Arabic language, to enrich the field of Arabic language studies.